Development of Optical Fiber Light-Transmitting Concrete (LTC)—A Review - Jian Bai; Weiguo Zhang; Jun Tian; Xiaowei Wu; Mingfang Zheng (Buildings)
In recent years, the use of new and unique building materials to achieve green building goals has attracted a lot of attention. Optical fiber light-transmitting concrete (LTC) makes it possible for light to pass through concrete. Its ornamental value and excellent light transmission have received much attention from scholars. However, the application of optical fiber LTC in the construction industry has not yet been promoted due to the tedious preparation process and insufficient research on its mechanical properties and durability. This paper reviews the research results of optical fiber LTC in terms of product preparation, light transmission, mechanical properties, durability, and microstructures. The light transmission of optical fiber LTCs is positively correlated with fiber content and negatively correlated with fiber diameter and fiber spacing. However, how the combination of these factors affects LTC transmittance remains to be investigated. In addition to fiber parameters, cement matrix properties and other environmental factors (light intensity, incidence angle, and aging) should also be considered to explore the suitability of LTC. The fiber–matrix interface bond strength needs further investigation and efforts should be made to improve it. This paper also summarizes the future challenges and research directions of optical fiber LTC, which is expected to provide guidance for the application of optical fiber LTC. It is anticipated that fiber-optic LTC will be promoted as a new building material.